PENGARUH PERCEIVED QUALITY, PERCEIVED RISK TERHADAP CUSTOMER TRUST DENGAN STORE IMAGE SEBAGAI VARIABEL MEDIASI PADA KONSUMEN SAYURAN ORGANIK MEREK FRESHARVEST DI KOTA BANDA ACEH - Agung Ade Yanuar Bulan; Sorayanti Utami (Departemen Manajemen, 2020)
The aim from research this is for knowing the effect of perceived quality, perceived risk on customer trust with image store as variable mediation . Research this do at 100 consumers at Suzuya Mall Banda Aceh. Retrieval sample use non probability sampling method . Research this use four variable , i.e. variable free , variable bound and variable mediation . Method analysis Hierarchical Linear Modeling (HLM) used as method analysis for knowing influence between variable free with variable bound . Questionnaire be measured use Likers Scale . Test validity , reliability , normality , and analysis regression use SPSS Statistics 20 . Results showing perceived quality have influence positive to customer trust; perceived risk have influence negative to customer trust ; perceived quality have influence positive to store image ; perceived risk have influence negative to store image; store image have influence positive to customer trust; store image mediate relationship between perceived quality and customer trust; store image mediate relationship between perceived risk and customer trust.